Association of type 2 diabetes mellitus with lung cancer in patients with chronic obstructive pulmonary disease - Kim, Nam Eun; Kang, Eun-Hwa; Ha, Eunhee; Lee, Ji-Young; Lee, Jin Hwa (Frontiers in Medicine, 2023)
Background: Patients with chronic obstructive pulmonary disease (COPD) have an increased risk of developing lung cancer. Some studies have also suggested that diabetes mellitus (DM) may increase the risk developing of lung cancer. This study aimed to investigate whether type 2 DM (T2DM) is associated with an increased risk of lung cancer in patients with COPD. Materials and methods: We conducted a retrospective analysis on two cohorts: the National Health Insurance Service-National Sample Cohort (NHIS-NSC) of Korea and the Common Data Model (CDM) database of a university hospital. Among patients newly diagnosed with COPD in each cohort, those with a lung cancer diagnosis were included, and a control group was selected through propensity score matching. We used the Kaplan–Meier analysis and Cox proportional hazard models to compare lung cancer incidence between patients with COPD and T2DM and those without T2DM. Results: In the NHIS-NSC and CDM cohorts, we enrolled 3,474 and 858 patients with COPD, respectively. In both cohorts, T2DM was associated with an increased risk of lung cancer (NHIS-NSC: adjusted hazard ratio [aHR], 1.20; 95% confidence interval [CI], 1.02 to 1.41; and CDM: aHR, 1.45; 95% CI, 1.02 to 2.07). Furthermore, in the NHIS-NSC, among patients with COPD and T2DM, the risk of lung cancer was higher in current smokers than in never-smokers (aHR, 1.45; 95% CI, 1.09 to 1.91); in smokers with ≥30 pack-years than in never-smokers (aHR, 1.82; 95% CI, 1.49 to 2.25); and in rural residents than in metropolitan residents (aHR, 1.33; 95% CI, 1.06 to 1.68). Conclusion: Our findings suggest that patients with COPD and T2DM may have an increased risk of developing lung cancer compared to those without T2DM.